SUPPORT SYSTEM FOR IRRIGATION SCHEDULING VIA SMS (SHORT MESSAGE SERVICE) - Rodrigues, Diogo Francisco Borba; Almeida, Ceres Duarte Guedes Cabral de; Batista, Maria da Conceição Moraes (IRRIGA, 2015)
In remote areas, especially in the north-east of Brazil, small farmers have difficulty in accessing information and obtaining technical assistance on irrigation. The purpose of this paper is to develop a decision support system for irrigation water management via SMS, called IGmanejo, that offers information and irrigation advice on the farmer’s mobile phone. Simulations were performed to evaluate water savings based on current and historical data comparing the values obtained by FAO CropWat 8.0 software. The greater water savings observed in the cycle that began in the transition season showed a reduction of 26%. The proposed software showed that it is able to reduce water waste in agriculture and send simple and quality irrigation advice to remote areas with a technology already assimilated in rural areas, that is, the mobile phone.